ANALYSIS OF TEACHER READINESS IN LEARNING WITH DIGITAL MEDIA IN ECONOMICS SUBJECT AT SMA NEGERI 10 PONTIANAK - Novitasary, Novitasary; Mashudi, Mashudi; Basri, Muhammad (Universitas Tanjungpura, 2023)
This research was conducted at SMA Negeri 10 Pontianak. The purpose of this study was to determine the readiness of lesson plans, worksheets, teaching materials, media and teacher evaluation in learning to use digital media in the subject of Economics at SMA 10 Negeri Pontianak. The research model is a qualitative approach in the form of a case study. The informants consisted of 2 economics teachers and 5 students. Data collection techniques using interviews, observation and documentation. This can be seen from the teacher still carrying out lesson plans even with the help of digital media by making lesson plans that adapt to conditions in the field, preparing teaching materials, preparing worksheets as a guide for students to follow subject matter in the form of textbooks, preparing media to convey subject matter other than by the manualway the teacher also conveys subject matter through digital media such as via YouTube, whatsapp groups, and google foam and the teacher also conducts learning evaluations to determine the level of success of students on the material that has been conveyed with the help of digital media such as filling out question material with Google foam.